Histomorphologic spectrum of thyroid lesions in surgically treated thyroid specimens - Haque, Wasim Selimul; Yasmin, Shamoli; Islam, SK Md Jaynul; Giti, Susane (BIRDEM Medical Journal, 2019)
Background: Diseases involving thyroid gland are myriad- they span from functional to goiterous which again can be non-neoplastic or neoplastic. The pattern and prevalence of these disorders depend on various factors like age, sex, ethnicity and geographic location of residence. The aim of the present study was to determine the pattern of thyroid lesions in surgically resected thyroid specimens. Methods: This retrospective study was conducted at Department of Histopathology ofArmed Forces Institute of Pathology (AFIP), Dhaka, Bangladesh. All thyroidectomy specimens received in the Department of Histopathology over the period from 1st January 2018 to 30th June 2019 were included in the study. Data including age, sex and histopathological diagnosis were collected from the records and histopathology slides of all cases were reviewed to verify diagnosis. Data were then analyzed by standard statistical methods. Results: A total of 377 specimens were collected, 301 specimens were from females and 76 from males (female to male ratio 4.01:1). The age ranged from 13 years to 82 years (mean 38.44±12.89 years). Nodular goiter (274, 72.62%) was the commonest thyroid lesion; other benign lesions included follicular adenoma (18) and Hashimoto thyroiditis (17). Overall malignancy was 18.03% (68). Papillary carcinoma (61, 89.70%) constituted majority of the malignant neoplasms. Other malignant neoplasms included follicular carcinoma (3 cases including 1 case of Hurthle cell carcinoma), anaplastic carcinoma (2) and medullary carcinoma and non-Hodgkin lymphoma 1 each. Conclusion: Our study revealed that the prevalent form of thyroid diseases is nodular goiter that mostly affects females. Papillary carcinoma is the commonest malignancy of thyroid gland which also predominantly affects females. Birdem Med J 2020; 10(1): 54-59